Sentence Comprehension in Primary Progressive Aphasia: A Study of the Application of the Brazilian Version of the Test for the Reception of Grammar (TROG2-Br) - Carthery-Goulart, Maria Teresa; de Oliveira, Rosimeire; de Almeida, Isabel Junqueira; Campanha, Aline; da Silva Souza, Dayse; Zana, Yossi; Caramelli, Paulo; Machado, Thais Helena (Frontiers in Neurology, 2022)
Sentence-comprehension deficits have been described in patients with primary progressive aphasia (PPA). However, most instruments to address this domain in more detail and in a clinical context have not been adapted and translated into several languages, posing limitations to clinical practice and cross-language research. Objectives The study aimed to (1) test the applicability of the Brazilian version of the Test for Reception of Grammar (TROG2-Br) to detect morphosyntactic deficits in patients with PPA; (2) investigate the association between performance in the test and sociodemographic and clinical variables (age, years of formal education, and disease duration); (3) characterize the performance of individuals presenting with the three more common variants of PPA (non-fluent, semantic, and logopenic) and mixed PPA (PPA-Mx) and analyze whether TROG-2 may assist in the distinction of these clinical profiles. Methods A total of 74 cognitively healthy participants and 34 individuals diagnosed with PPA were assessed with TROG2-Br. Overall scores (correct items, passed blocks), types, and categories of errors were analyzed. Results In controls, block scores were significantly correlated with years of formal education (Spearman's r = 0.33, p = 004) but not with age. In PPA, age, education, and disease duration were not significantly associated with performance in the test. Controls presented a significantly higher performance on TROG2-Br compared to PPA individuals and their errors pattern pointed to mild general cognitive processing difficulties (attention, working memory). PPA error types pointed to processing and morphosyntactic deficits in nonfluent or agrammatic PPA, (PPA-NF/A), logopenic PPA (PPA-L), and PPA-Mx. The semantic PPA (PPA-S) subgroup was qualitatively more similar to controls (processing difficulties and lower percentage of morphosyntactic errors). TROG2-Br presented good internal consistency and concurrent validity. Discussion Our results corroborate findings with TROG-2 in other populations. The performance of typical older adults with heterogeneous levels of education is discussed along with recommendations for clinical use of the test and future directions of research.